Women's justice and protection in family law: A normative examination of the principles of the qur'an answers the accusation of patriarchal bias - Hevrialni, Rully; Hidayatullah, Hidayatullah (Privietlab, 2026)
This study is motivated by the growing accusation that Islamic family law is inherently patriarchal and fails to protect women adequately. Such criticisms arise from the gap between Qur'anic principles of justice and socio-cultural practices, as well as traditional interpretations shaped by patriarchal structures. In response to this issue, this study aims to re-examine the principles of justice and women's protection in the Qur'an using a normative approach combined with Qur'anic feminist perspectives. The central question addressed is whether the Qur'anic text itself supports patriarchy or whether patriarchal tendencies originate from historical interpretations and cultural practices surrounding the text. This research employs a qualitative method using library research and thematic content analysis (maudhu'i). The primary data consisted of Qur'anic verses related to gender relations, marriage, divorce, and family responsibilities, while the secondary data included classical and contemporary tafsir literature as well as feminist Islamic scholarship. The analysis focuses on identifying patterns of meaning, moral objectives (maqāṣid), and substantive justice embedded within the Qur'anic discourse. The findings reveal that the Qur'an is inherently anti-patriarchal and strongly upholds principles of justice, reciprocity, and the protection of women's dignity. Verses such as Qur'an 4:1, 4:19, 2:231, and 9:71 emphasize women's spiritual, social, and economic rights. The study concludes that patriarchal bias does not originate from the Qur'anic text itself but from socio-historical interpretations shaped by patriarchal contexts. Therefore, reconstructing Islamic family law based on maqāṣid al-Qur'an is essential for developing a more just, humane, and gender-responsive model of family relations aligned with the Qur ‘an’s ethical spirit.